Factors affecting on employee readiness: a case study among management undergraduates in Sri Lanka - Nanayakkara G. P. S. S. Theekshana Suraweera, Waththage Vidarshika; Dewasurendra M. T.; Perera, C.M.S.; Shiwangi S G R; Suraweera, T.; Vidarshika, W. (Sri Lanka Institute of Information Technology : Malabe, 2025)
The employability of business management graduates in Sri Lanka is a growing concern due to a disconnect between higher education outcomes and labor market demands. Despite increasing graduation rates, many struggle to secure suitable jobs due to skill gaps in practical competencies and workplace readiness. Employers frequently report dissatisfaction with graduates' deficiencies in communication, teamwork, leadership, technological adaptability, problem-solving, and self management skills, which are essential in today’s dynamic business environment. This study explores the root causes of mismatch by analyzing qualitative data from recruitment professionals and HR managers. For this, primary data was collected through semi-structured interviews with industry experts and HR professionals from 15 private sector companies using the snowball sampling method and based on data saturation. The data was analyzed through thematic analysis, which identified seven key competencies that employers expect from employees: communication skills, problem solving skills, adaptability and learning skills, teamwork and leadership, emotional intelligence, information management skills, and self-management. The research points to systemic issues in higher education, where curricula often emphasize theory over practical application, leaving graduates unprepared for real-world business challenges. By outlining the competencies most valued by employers, this study offers insights for educational institutions to align their programs with industry needs. Bridging this gap is crucial for improving employability, fostering economic growth, and reducing graduate unemployment in Sri Lanka. The findings contribute to discussions on education reform, workforce development, and policy interventions to create a more responsive and competitive labor market.
Keywords: Employability; Employability of graduates; Employability skills; Employee readiness